FOURIER TRANSFORM SOLUTIONS FOR NONLINEAR THERMAL BOUNDARY LAYER FLOWS USING FUZZY NUMERICAL METHODS - T N, Vasanthakumari (ShodhKosh: Journal of Visual and Performing Arts, 2022)
It is introduced an innovative method for modeling nonlinear flows with thermal boundary layer by combining Fourier transforms and fuzzy numerical methods. The nonlinear energy and momentum equations are transformed into spectral domain using Fourier transform, while fuzziness in parameters like slip velocity and thermal diffusivity are treated with fuzzy logic. The proposed framework can well capture the nonlinear effect in uncertain environments, and does a better job than the classical deterministic model in term of accuracy and computational efficiency. Relevance to real applications (such as aerodynamics, microfluidics, thermal engineering, etc.) is demonstrated with experiments validating the model. These findings highlight the application of these hybrid methodology toward enhancing energy systems, material processes, and other thermal applications. Future work entails generalizing the method to turbulent flows, sophisticated fuzzy models, and multi-disciplinary applications.